ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN PENDAPATAN ASLI DAERAH TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL DI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT TAHUN 2009-2013 - B01111123, YADI HARTONO (Jurnal Pembangunan dan Pemerataan, 2016)
This study aims to investigate the effect of economic growth and the local revenue againts thecapital expenditure budget allocation in the District/City of West Kalimantan Province in 2009 to2013.The method used in this research is descriptive quantitative method that applies panel data bycombining data time series and cross section from 2009 to 2013 and the data is obtained from theCentral Statistics Agency of West Kalimantan. The analysis in this study employs multiple linearregression analysis. Once the data is collected, the data is analyzed by using Eviews 6 to testeconomic growth and the local revenues againts the capital expenditures partially t-test orsimultaneously F-test.The results show that economic growth has a negative relationship and does not have a significanteffect on the allocation of capital expenditure, this is evidenced by a value of -0,862094, Meanwhilelocal revenue has a positive relationship and demonstrates a significant effect againts the allocationof capital expenditure, this is indicated by the acquistion value of 3,183926.Keywords: Capital Expenditure, Economic Growth and Local Revenue (PAD)